PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN PEGAWAI TELADAN MENGGUNAKAN METODE SAW (SIMPLE ADDITIVE WEIGHTING) BERBASIS WEB DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN KEBUMEN - Waluyo, Ari; Fais Irfandi, Nur (Politeknik Dharma Patria Kebumen, 2019)
The purpose of this research is to design decision support system of exemplary web-based employee using SAW (Simple Additive Weighting) method in capital investment and integrated service one door regency kebumen. Calculation method used is SAW (Simple Additive Weighting) method. Data collection techniques used is by observation, literature study and interviews that have a close relationship with the principal problems and methods of system development used is the method of waterfall system development. From the results of research conducted found the problems such as the lack of effective selection of exemplary employees who performed because it is still manual so that the selection of exemplary employees are still not efficient. The suggestions given to overcome the problem are: 1) Need to be socialized and training to the related sections, especially on the Subdivision of Personnel and general as admin, so that information systems can be utilized properly, 2) Need a better system development for data security can be more awake.